Internal communication in the Spain national health system - Bustamante Ospina, Edilson (Folios, revista de la Facultad de Comunicaciones y Filología, 2013)
This paper analyzes the role of internal communication in the context of the Spain National Health System, particularly in the stages of Family Practice and Specialized Care. Internal communication is studied as a part of health communication processes that can help promote and achieve the objectives of the health institutions. The analysis shows the main results up to date and propose what should be some guidelines for internal communication in Spain Health System scenes. The findings call for the need of an internal communication policy that, among other things, work from lines such as the role of leaders, the integration of employees, their identification with what they do, and the investigation of communication processes.